Shape Parameter of Extended Uniform Cubic B-Spline in Designing Three Dimensional Objects - Mohamad Sukri, Nursyazni; Khairiah Razali, Noor; Musliha Nor-Al-Din, Siti; Afzanurfahmi Che Adnan, Muhammad; Abdul Hadi, Normi; ., . (International Journal of Engineering and Technology, 2018)
In Computer Aided Geometric Design (CAGD), B-spline curves are piecewise polynomial parametric curves that play an important role. CAGD which has been widely used, brings the good impact of computers to industries such as automobile. To meet engineering requirements, Extended Cubic Uniform B-Spline is proposed to be applied in creating new objects. Furthermore, three dimensional objects such as rod, bottle and others can be generated from Extended Cubic Uniform B-Spline curves by using translation technique of sweep surface method. In this research, the three-dimensional objects are formed by transforming Extended Cubic Uniform B-Spline with degree 4 by using translation technique. The advantage of using Extended Cubic Uniform B-Spline is the curve can be modified by changing the value of shape parameter. Various shapes of three dimensional objects can be formed by using different shape parameters. The smoothness of three dimensional objects is analyzed by shape parameter value from Â to . The result shows object with and Â are smooth.Â Â